Decoding the Cognitive Poetics of the Pantun: Stylistic Constraints, Semantic Mapping, and Cultural Identity Construction - Timanta Agustina Br Purba; Rosmawaty Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Recognized globally as an intangible cultural heritage, the pantun remains a vital instrument for sustaining social harmony, collective memory, and cultural identity across the Indonesian archipelago. Yet, conventional literary criticism frequently reduces this vibrant oral tradition to its rigid formalistic structures, specifically its alternating rhyme schemes and strict syllable counts. This reductionism ultimately overlooks the dynamic socio-cognitive functions of the genre within contemporary discourse. This study directly challenges these formalist limitations. By deploying a hybrid framework of stylistics and cultural poetics, we investigate how distinct linguistic styles and thematic variations operate as active mechanisms for identity negotiation. Operating within a qualitative, descriptive-interpretative paradigm, we subjected sixty purposively sampled pantun stanzas from verified archival anthologies to a close, granular textual analysis. The empirical findings demonstrate that the pantun functions as a highly contested site of ideological negotiation, systemic social critique, and behavioral modification. Structurally, the deliberate semantic tension between the natural imagery of the sampiran (preparatory couplet) and the didactic weight of the isi (core message) establishes an associative cognitive bridge. This mechanism facilitates non-confrontational communication and the seamless transmission of communal ethics. Ultimately, this study offers a fresh trajectory for understanding how rigid poetic constraints adapt to modern communicative imperatives, providing a scalable framework to integrate traditional orality into contemporary applied linguistics and literary pedagogy.